Integration of Single Atoms for Tandem Catalysis - Liu, Cun; Qiao, Botao; Zhang, Tao (JACS Au, 2024)
Tandem catalysis represents an efficient pathway which greatly saves the overall facilities and energy inputs. The intermediates are transported from one active site to the other site more efficiently due to the ease of mass transfer in one reactor system. However, sometimes the indiscriminative usage of this concept can be misleading, and thereby, this Perspective first aims for differentiating “tandem catalysis” from liable-to-muddling concepts, such as “synergy” and “domino/cascade catalysis.” The prerequisites for figuring out tandem catalysis mainly lie in (1) the two or more independent catalytic cycles involved in one system, where the products of one reaction cycle can be immediately relayed to a subsequent reaction cycle as the reactants, and (2) these cycles occurring in different catalytic mechanisms. As a frontier in heterogeneous catalysis, single-atom catalysts possess the unique property of high selectivity toward transformation of specific chemical bonds and can also bridge the homo- and heterogeneous catalysis. However, despite their wide range of applications, single-atom catalysts (SACs) are not solutions to all catalytic processes, particularly those reactions requiring active sites containing multiatoms in their proximity. To this end, the strategy of combining SACs within tandem processes is a feasible way to broaden the scope of chemical reactions achievable over SACs. Therein, according to the category of the participating active species, four subsections are thoroughly introduced, including tandem catalysis over the integration of (1) different/identical single atom(s), (2) single atoms and nanoparticles, and (3) single atoms and the adjacent support. Nonetheless, with regard to the investigation of the involved single-atom catalysts, some issues still remain regarding the exact characterization and explicit comparison of catalytic performance with that over their nanoparticle counterparts. Moreover, some intriguing subjects are still waiting to be systematically explored to broaden and deepen single-atom-integrated tandem processes in the branch of catalytic science.